2015
DOI: 10.1089/jmf.2014.3380
|View full text |Cite
|
Sign up to set email alerts
|

Maltitol Prevents the Progression of Fatty Liver Degeneration in Mice Fed High-Fat Diets

Abstract: Nonalcoholic fatty liver disease (NAFLD) progresses to nonalcoholic steatohepatitis, ultimately leading to cirrhosis and liver cancer. It is important to prevent this progression during the initial stages of hepatic fatty degeneration. Maltitol is a polyol produced by the hydrogenation of maltose. We investigated the efficacy of maltitol for treating hepatic fatty degeneration in C57BL/6 male mice using a high-fat diet model. Intake of 5.0% maltitol for 8 weeks significantly suppressed weight gain, hepatic fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…On the other hand, triglyceride and fatty acid metabolism are also regulated by FXR. Urushima et al found that dietary maltitol decreased the expression of SREBP1c and increased the expression of PPARα in the liver in a high-fat diet mice model, which were speculated to be correlated with the suppression of hepatic FXR . PXR mediated the relation between FXR and the activation of lipogenic transcriptional factor SREBP1c and deactivation of PPARα. ,, Thereby, FXR is one approach for fighting lipid accumulation through suppressing PPARγ and SREBP1c expression and increasing PPARα expression.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, triglyceride and fatty acid metabolism are also regulated by FXR. Urushima et al found that dietary maltitol decreased the expression of SREBP1c and increased the expression of PPARα in the liver in a high-fat diet mice model, which were speculated to be correlated with the suppression of hepatic FXR . PXR mediated the relation between FXR and the activation of lipogenic transcriptional factor SREBP1c and deactivation of PPARα. ,, Thereby, FXR is one approach for fighting lipid accumulation through suppressing PPARγ and SREBP1c expression and increasing PPARα expression.…”
Section: Discussionmentioning
confidence: 99%
“…A similar result was shown with dietary sorbitol and xylitol which decreased plasma triglyceride and cholesterol, and fat tissue weights in rats [ 142 ]. Matitol supplementation suppressed weight gain, hepatic fat degeneration, hyperglycemia and hypercholesterolemia in mice fed high-fat diets [ 143 ] In addition, the epilactose in the diet lowered the levels of plasma total cholesterol and low-density lipoprotein cholesterol in rats [ 144 ]. Dietary FOS also showed a hypolipidemic effect in rats, for example, decreasing total cholesterol and triglycerides in blood [ 145 ].…”
Section: Effects On Nutrient Digestion Absorption and Systemic Mmentioning
confidence: 99%
“…A study by Urushima et al [ 109 ] demonstrated that supplementation with maltitol suppressed obesity, hyperglycemia, hypercholesterolemia, and fatty liver degeneration in mice fed a high-fat diet. Therefore, maltitol may be useful for treating patients in the initial stages of fatty liver disease to improve steatohepatitis.…”
Section: Sweetenersmentioning
confidence: 99%